Critically-enhanced nonreciprocal electronic transport at magnetic phase boundary in a room temperature helimagnet YMn_{6}Sn_{6} - Hidetoshi Masuda; Jun-ichiro Ohe; Yoichi Nii; Shojiro Kimura; Yoshinori Onose (Physical Review Research)
We investigated nonreciprocal electronic transport, a diode effect of electric current flow, in a helimagnet YMn_{6}Sn_{6}. We found that nonreciprocal resistivity, whose sign depends on the handedness of the magnetic spiral (chirality), was drastically enhanced in the vicinity of the helimagnetic transition magnetic field. This critical enhancement was observed in the wide temperature range below the helimagnetic transition temperature 335 K. We comparatively discuss three possible mechanisms of nonreciprocal electronic transport: band asymmetry, current-induced deformation of the magnetic structure, and asymmetric scattering, and suggest the most plausible mechanism is the last one.